2014
DOI: 10.1021/es5044358
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Isotope Signatures in Contaminated Sediments as a Tracer for Local Industrial Pollution Sources

Abstract: Mass-dependent fractionation (MDF) and mass-independent fractionation (MIF) may cause characteristic isotope signatures of different mercury (Hg) sources and help understand transformation processes at contaminated sites. Here, we present Hg isotope data of sediments collected near industrial pollution sources in Sweden contaminated with elemental liquid Hg (mainly chlor-alkali industry) or phenyl-Hg (paper industry). The sediments exhibited a wide range of total Hg concentrations from 0.86 to 99 μg g(-1), con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 56 publications
6
60
0
Order By: Relevance
“…It was recently shown that Hg adsorbed on iron oxyhydroxide (goethite) is depleted in 202 Hg relative to dissolved species (Jiskra et al, 2012), potentially creating a pool of dissolved inorganic Hg that is enriched in 202 Hg and available to microorganisms. However, in estuarine sediments, organically-bound inorganic Hg was found to have lower δ 202 Hg values than the presumably less bioavailable sulfidebound Hg (Wiederhold et al, 2015). Finally, another factor that may explain the range of MeHg isotopic compositions we observed are differences in Hg fractionation factors among the dominant species of microbes catalyzing Hg methylation and demethylation in the environment.…”
Section: Sitementioning
confidence: 71%
“…It was recently shown that Hg adsorbed on iron oxyhydroxide (goethite) is depleted in 202 Hg relative to dissolved species (Jiskra et al, 2012), potentially creating a pool of dissolved inorganic Hg that is enriched in 202 Hg and available to microorganisms. However, in estuarine sediments, organically-bound inorganic Hg was found to have lower δ 202 Hg values than the presumably less bioavailable sulfidebound Hg (Wiederhold et al, 2015). Finally, another factor that may explain the range of MeHg isotopic compositions we observed are differences in Hg fractionation factors among the dominant species of microbes catalyzing Hg methylation and demethylation in the environment.…”
Section: Sitementioning
confidence: 71%
“…By plotting Δ 202 Hg versus Δ 199 Hg signals, the three Hg sources are characterized by distinct “ δ 202 Hg‐Δ 199 Hg” signatures (Figure ). The isotopic signature of industrial Hg can be estimated using Hg polluted sediments with their locations in the vicinity of known industrial sources (Balogh et al, ; Bartov et al, ; Bonsignore et al, ; Cooke et al, ; Donovan et al, ; Guédron et al, ; Ma et al, ; Mil‐Homens et al, ; Gray et al, ; Perrot et al, ; Sonke et al, ; Wiederhold et al, ; Yin et al, ), and hydrothermal ores which are the major source of Hg used in industry (Blum & Bergquist, ; Cooke et al, ; Feng et al, ; Foucher & Hintelmann, ; Gray et al, ; Smith et al, ; Stetson et al, ; Wiederhold et al, ; Yin et al, ). Based on the summarization of previous data, we estimated that industrial Hg has mean δ 202 Hg of −0.53 ± 0.51‰ and mean Δ 199 Hg of −0.02 ± 0.11‰ (σ, n = 481).…”
Section: Resultsmentioning
confidence: 99%
“…Journal of Geophysical Research: Oceans Cooke et al, 2013;Donovan et al, 2013;Guédron et al, 2016;Ma et al, 2013;Mil-Homens et al, 2013;Gray et al, 2015;Perrot et al, 2010;Sonke et al, 2010;Wiederhold et al, 2015;Yin et al, 2016a), and hydrothermal ores which are the major source of Hg used in industry Cooke et al, 2013;Feng et al, 2010;Foucher & Hintelmann, 2009;Gray et al, 2013;Smith et al, 2008;Stetson et al, 2009;Wiederhold et al, 2013;Yin et al, 2013Yin et al, , 2016c. Based on the summarization of previous data, we estimated that industrial Hg has mean δ 202 Hg of À0.53 ± 0.51‰ and mean Δ 199 Hg of À0.02 ± 0.11‰ (σ, n = 481).…”
Section: 1029/2017jc013691mentioning
confidence: 95%
“…23,30 The Hg isotopic composition of sediment has previously been used to identify anthropogenic Hg sources and trace their transport and deposition in river and estuarine environments. [31][32][33][34][35] Hg isotopes have also been measured in a variety of Hg mine waste materials, including calcines and CA Coast Range Hg-ores. [36][37][38][39][40] Hg mine wastes can vary widely in isotopic composition over very small spatial scales (e.g., δ 202 Hg range of >5‰ within a single calcine sample), 31,32 but sediment downstream of individual mines is thought to largely integrate these different mining sources.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] Hg isotopes have also been measured in a variety of Hg mine waste materials, including calcines and CA Coast Range Hg-ores. [36][37][38][39][40] Hg mine wastes can vary widely in isotopic composition over very small spatial scales (e.g., δ 202 Hg range of >5‰ within a single calcine sample), 31,32 but sediment downstream of individual mines is thought to largely integrate these different mining sources. 35,39,41 We hypothesized that the isotopic composition of high THg sediment in Cache Creek downstream of individual mining districts would enable us to distinguish the contribution of Hg mining (Coast Range) vs. Aumining (Sierra Nevada) Hg sources to Yolo Bypass.…”
Section: Introductionmentioning
confidence: 99%